27 August 2001 substorm: Preonset phenomena, two main onsets, field‐aligned current systems, and plasma flow channels in the ionosphere and in the magnetosphere. Issue 5 (5th May 2017) - Mishin, V. M.; Mishin, V. V.; Lunyushkin, S. B.; Wang, J. Y.; Moiseev, A. V.
Abstract: We supplement the results of the 27 August 2001 substorm studied earlier in the series of papers. Described is the plasma flow in the nightside ionosphere from the near‐polar region from the polar cap to the auroral oval during the substorm preonset phase and two expansion onsets, EO1 and EO2, produced by reconnection in the closed tail (magnetic reconnection (MR1) and in the open tail lobes (MR2), respectively. We discuss the location of the MR2 region (is it near, middle, and/or distant tail?) and the EO2 trigger mechanism. The upward substorm current wedge field‐aligned current (FAC) and the downward FAC in the polar cap dusk sector that were both produced by different types of magnetosphere‐ionosphere feedback instability are found to provide the main contribution to the system of FACs during EO1 and EO2. Also, we obtain the estimates for the EO1 and EO2 power and energy. Addressed are the variations in the tail lobe magnetic flux and their (variations) association with EO2. In addition, we describe a 3‐D system of mesoscale cells, each of which involves a plasma vortex and a local FAC maximum. The cells of this system in the inner magnetosphere and in the tail lobes intensify one after other within 2 min interval. At last, we substantiate the assumption that the fast plasma flow recorded by the Cluster satellites 7 min prior to EO1 was a bursty bulk flow from the most distant tail. Key Points: M‐I feedback instability was associated with expansion onsets in this substorm Expansion onsets in closed tail and open tail lobes were observed in different times and places BBF in the midtail is described as a continuation of the plasma flux from the distant tail